Long non-coding RNA LINC01224 promotes progression and cisplatin resistance in non-small lung cancer by sponging miR-2467. (October 2021) - Xiao, Shumei; Sun, Longhua; Ruan, Bin; Li, Junhe; Chen, Jun; Xiong, Jianping; Jiang, Yanxia; Song, Zhiwang
Abstract: Copious evidence reveals that long non-coding RNAs (lncRNAs) exert great regulatory functions in various human cancers. LINC01224 is a novel lncRNA, identified as a cancer regulator of HCC. However, the underlying mechanisms and clinical significance of LINC01224 in other types of cancers need further researches to explore. In this study, we aimed to elucidate the biological role of LINC01224 in NSCLC progression. Presently, LINNC01224 expression was elevated and miR-2467 expression was down-regulated in NSCLC, compared with standard control. Then we described the reciprocal correlation between LINC01224 and miR 2467. Afterward, the dual-luciferase reporter assay, RIP assay and RNA pull-down assay validated the base-pair interaction between LINC01224 and miR-2467. Moreover, our findings demonstrated that the silence of LINC01224 inhibited cell proliferation and invasion in NSCLC and enhanced cisplatin (CDDP) sensitivity in vitro . Besides, rescue assays verified that miR-2467 inhibitor could reverse the effects on cell biological activities and CDDP resistance caused by knockdown of LINC01224. Finally, in vivo experiments implicated that knockdown of LINC01224 could inhibit NSCLC tumor growth. To sum up, LINC01224 can promote tumor progression and CDDP resistance in NSCLC via sponging miR-2467, suggesting a promising therapeutic target for better diagnosis and prognosis of NSCLC patients.